Formulation And Evaluation Of Osmotically Controlled Oral Drug Delivery System Of Salbutamol Sulphate - Devipriya.U, Devipriya.U; Sathali, A. Abdul Hassan; A. Vijayalakshmi, A. Vijayalakshmi (Journal of Neonatal Surgery, 2025)
Osmotically Controlled Release Tablets (OCRT) of Salbutamol Sulphate (SS) that achieve zero-order drug release, independent of gastrointestinal physiological factors were formulated and evaluated in this study. SS is a highly water-soluble drug, leading to rapid release and absorption when administered orally. To mitigate this, the study aimed to control the drug's release rate using an osmotic pump system and to arrive at an optimal formulation by assessing the effect of varying concentration & type of osmogen and the size of orifice on the release rate of the drug. Core tablets containing Salbutamol sulphate and varying concentrations of different types of osmogens (Sodium Chloride (NaCl), Potassium Chloride (KCl) and Sodium Chloride – Potassium Chloride (1:1) mixture) were prepared and covered by a semipermeable coating membrane composed of cellulose acetate and Poly Ethylene Glycol (PEG) 400. Delivery orifices of different sizes (0.2mm, 0.4mm and 0.6mm) were created on the coating one side of the tablets forming an Elementary Osmotic Pump System. The 30 OCRT formulations were evaluated for physicochemical properties and In vitro drug release, which was then compared to a marketed controlled-release product. Scanning Electron Microscopy (SEM) was used to examine the membrane morphology and orifice size. Short-term stability studies were also conducted under extreme condition for 60 days. The study revealed that the OCRT of SS with higher concentration (75%w/w) of NaCl and a 0.4mm Orifice exhibited optimal controlled release properties. SEM analysis confirmed the consistency and integrity of the membrane and orifice. Stability studies indicated that the optimized formulation remained stable under extreme conditions for 60 days. The study demonstrates that the type and concentration of osmogen, along with the orifice diameter, are critical factors in controlling the release rate of Salbutamol Sulphate in OCRT formulations. The optimized formulation achieved a zero-order release profile, offering a potential improvement over existing controlled-release products.